Plan de marketing digital para fomentar el turismo en el cantón Yantzaza provincia de Zamora Chinchipe - Lozano Morocho, Teresa Natividad (2024)
The aim of this thesis was to develop a digital marketing plan to promote tourism in the San Vicente de Caney community, located in the Yantzaza canton, Zamora-Chinchipe province, for the period of January to June 2024. The plan aims to demonstrate the region's tourism potential by highlighting its subtropical natural environment, abundant vegetation, diverse fauna, rivers, waterfalls, and caves geographical features of the area that should be leveraged by tourists from around the world. The research undertaken is of a descriptive-relational nature, utilizing survey and interview techniques, which were applied to the population of Yantzaza. The findings indicate that digital promotion is a critical factor in facilitating tourism activities. Additionally, the most widely used social media platforms are Facebook, YouTube, and WhatsApp, with a readiness to receive information occasionally through these platforms. Consequently, the validation of the proposed idea is recommended, and a digital marketing plan is presented, followed by a structured proposal. The SWOT matrix, encompassing strengths, opportunities, weaknesses, and threats, is also detailed. In this manner, the strategic SWOT is formulated, contributing to the development of strategies that enhance the positioning of the region's tourist attractions and improve their visibility in both local and international markets. This plan further explores how digital tools can help reach broader audiences, engage potential visitors, and foster long-term growth in the tourism sector. Keywords: digital marketing, tourism, marketing strategies, tourism, community participation, market growth